An Integrated Policy Model for Supervisory Punishment under Indonesia's New Criminal Code - Rohmat Rohmat; Milda Istiqomah; Nurini Aprilianda (Jurnal Penelitian Hukum De Jure, 2025)
The inclusion of supervisory sanctions in Indonesia's new Criminal Code signifies a shift toward non-custodial and rehabilitative forms of punishment, reflecting a broader transition from retributive to corrective and restorative justice. Despite their formal adoption, the regulatory frameworks necessary for their implementation remain underdeveloped. This study examines the normative and philosophical foundations of supervisory sanctions and proposes an integrated legal policy model for their effective application. Employing a normative juridical method supported by statutory, comparative, and conceptual approaches, the research is analyzed within a prescriptive framework. The findings indicate that these sanctions are intended to provide offenders with a second chance through structured oversight and individualized rehabilitation, thereby avoiding incarceration. This study offers a novel insight by presenting an integrated policy model for supervisory sanctions, an approach that has not previously been developed within Indonesia's legal system. The proposed model outlines mechanisms for enforcement, supervision duration, and reintegration programs. By addressing a critical gap in Indonesia's penal system, this research contributes original perspectives and a practical framework for the operationalization of community-based criminal sanctions.